2022
DOI: 10.47853/fas.2022.e48
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility coefficients of animal feed ingredients for olive flounder (Paralichthys olivaceus)

Abstract: Apparent digestibility coefficients (ADCs) of dry matter, crude protein, crude lipid, nitrogen-free extract, energy and essential amino acids in animal-based feed ingredients were determined for olive flounder (Paralichthys olivaceus). A reference diet (RF) was formulated to contain 1.0% chromic oxide (Cr 2 O 3 ) as an inert indicator. Nine test diets were formulated to contain RF and one of the feed ingredients (pollock meal [PM], jack mackerel meal [JMM], anchovy meal [AM], cod meal [CM], sardine meal [SM], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…MM also exhibited high-pepsin digestibility which was comparable to sardine FM and SPC ( Table 2 ). Rahman et al [ 15 ] reported that nutrient digestibility of MM (84% CP) was higher in olive flounder compared to different conventional FM. Therefore, nutrient digestibility of diets might be improved by MM in red seabream to observe higher growth performance and feed utilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MM also exhibited high-pepsin digestibility which was comparable to sardine FM and SPC ( Table 2 ). Rahman et al [ 15 ] reported that nutrient digestibility of MM (84% CP) was higher in olive flounder compared to different conventional FM. Therefore, nutrient digestibility of diets might be improved by MM in red seabream to observe higher growth performance and feed utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Supportively, DFI of fish was not significantly different among treatments while FE was higher in fish-fed diets containing MM except for CMM. Animal protein sources contain a more balanced nutrient profile compared to plant protein sources [ 15 , 37 ]. Lu et al [ 38 ] observed that growth performance and FE of rainbow trout were increased by animal protein sources more efficiently than plant protein sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors are known to influence the digestibility of a given dietary ingredient. Among those criteria are the type of ingredient and the degree of processing utilized to produce it, as well as the source and quality of the original raw material used [ 32 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%